B-cell repertoire responses to varicella-zoster vaccination in human identical twins - Wang, Chen; Liu, Yi; Cavanagh, Mary M.; Le Saux, Sabine; Qi, Qian; Roskin, Krishna M.; Looney, Timothy J.; Lee, Ji-Yeun; Dixit, Vaishali; Dekker, Cornelia L.; Swan, Gary E.; Goronzy, Jörg J.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
Adaptive immune responses in humans rely on somatic genetic rearrangements of Ig and T-cell receptor loci to generate diverse antigen receptors. It is unclear to what extent an individual’s genetic background affects the characteristics of the antibody repertoire used in responding to vaccination or infection. We studied the B-cell repertoires and clonal expansions in response to attenuated varicella-zoster vaccination in four pairs of adult identical twins and found that the global antibody repertoires of twin pair members showed high similarity in antibody heavy chain V, D, and J gene segment use, and in the length and features of the complementarity-determining region 3, a major determinant of antigen binding. These twin similarities were most pronounced in the IgM-expressing B-cell pools, but were seen to a lesser extent in IgG-expressing B cells. In addition, the degree of antibody somatic mutation accumulated in the B-cell repertoire was highly correlated within twin pair members. Twin pair members had greater numbers of shared convergent antibody sequences, including mutated sequences, suggesting similarity among memory B-cell clonal lineages. Despite these similarities in the memory repertoire, the B-cell clones used in acute responses to ZOSTAVAX vaccination were largely unique to each individual. Taken together, these results suggest that the overall B-cell repertoire is significantly shaped by the underlying germ-line genome, but that stochastic or individual-specific effects dominate the selection of clones in response to an acute antigenic stimulus. Significance Human B cells secrete highly diverse antibody molecules to recognize and defend against infectious agents. Developing B cells independently rearrange their genomes to produce antibody-encoding sequences. It is uncertain to what degree genetic factors control antibody repertoires and the antibodies elicited by defined antigenic stimuli. Analysis of 134,000 antibody heavy chain sequences from genetically identical twins vaccinated with varicella-zoster vaccine indicates that twins show increased correlation in antibody gene segment usage, junctional features, and mutation rates in their antibody pools but show little similarity in clonal responses to an acute stimulus. Therefore, a shared germ-line genome sequence is correlated with overall convergence of antibody repertoires, but the particular antibody response to a given vaccination is less predictable.